Clinicopathological study of salivary gland tumors: An observation in tertiary hospital of central India - Rajdeo, Roma Nirmalkumar; Shrivastava, Alok C; Bajaj, Jitin; Shrikhande, Anuradha V; Rajdeo, Ravi N (International Journal of Research in Medical Sciences, 2017)
Background: The salivary glands are one of the few tissues in the body that are subjected to diverse and heterogeneous range of tumors and tumor like conditions. The relative infrequency of these tumors makes their diagnosis and management quite complicated. Fine needle aspiration cytology (FNAC) is a useful diagnostic procedure which has a recognized role in the evaluation of salivary gland lesions. A pre-operative diagnosis about nature of lesion, whether benign or malignant, will help in making decision about proper management of patient. Objective: Aim of this study was to know the epidemiology of salivary gland tumors in our region and to evaluate sensitivity, specificity and diagnostic accuracy of fine needle aspiration cytology taking histopathology as the gold standard. Method: It was prospective observational study conducted in department of pathology in our institute. Total 100 cases were studied with particular reference to age, sex, site, cytologic details & histological types as per WHO classification. FNAC & histopathological examination was done in all cases. Correlation between cytological & histopathological diagnoses was assessed. Diagnostic accuracy of FNAC was evaluated by comparing cytological & histopathological diagnoses. Results: Parotid gland was the most common site of involvement (70% cases). Maximum number of patients was in age range of 41-50 years & male to female ratio was 0.8:1. Most common benign & malignant tumors were pleomorphic adenoma (69.89% cases) & mucoepidermoid carcinoma (8.60% cases) respectively. On cytology, 93 cases while on histopathology 96 cases were diagnosed as neoplastic. Cytological diagnoses correlated with histopathological diagnoses in 94% cases. Sensitivity, specificity & diagnostic accuracy of FNAC were found to be 96.87%, 100% & 96% respectively. Conclusion: FNAC in salivary gland masses is fairly reliable for correct preoperative diagnosis. Multiple sampling and special attention to cytologic features should help to minimize errors.